Measuring market integration and pricing efficiency along regional maize-tortilla chains of Mexico - Valdes Salazar, Rodrigo (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
When market performance is analyzed, a key issue to understand is the extent to which different agents in the supply chain respond to changes in price shocks. This paper explores the Mexican maize–tortilla chain through a price transmission analysis. It focus on a country-level study of the Mexican tortilla market by considering different regions and commercialization chains. Using a Vector Error Correction Model (VECM) the integration of the Mexican maize tortilla market betweenthe inter-region tortillería, inter-region supermarket and intra-region tortillería-supermarket prices are investigated. The findings suggest that price transmission between tortillerías and supermarkets within a region seems to have triggered a shift in some consumers’ place of purchase. Moreover, it demonstrates that cointegration level mainly depends of storage, logistics and transportation that could be the reason for the upsurge in variability of tortilla prices between states. These results appear to validate that radial transportation system in Mexico has benefited the central regions at the expense of the periphery regions, thus enabling tortillerías in Central regions to remain competitive with supermarkets and retain their market share.